(untitled) (Al-Qamar, 2021)
With the passage of time, the universe is in a constant state of expansion. Humanity has experienced tremendous progress from the dawn of time until the present. This journey of human progress is rapidly moving forward. This is a reality that we cannot deny. However, on the contrary the condition of Muslim Ummah is such that the Muslims seem to be stuck in the Stone Age. Despite having numerous resources, the Muslim Ummah is facing a lot of difficulties and challenges. Everywhere, the Muslims are being annihilated mercilessly. On the other hand, the enemies can attack any Muslim country as and when they wish. No law, no humanity and no morality can stop them from carrying out this brutal act. Today, the Muslim Ummah is not facing this problem because of their number but they are affected economically, socially, morally, religiously and politically due to their own mistakes. One of the major causes is the political instability. If the Muslim Ummah gets politically stable, all the issues will be resolved automatically. When our Holy Prophet (SAAS) came to Madinah, He, first established the political state and ensured its stability. Due to this act, all the other issues started getting resolved easily with the passage of time. The darkness has engulfed the Muslim world with no sight of dawn in the near future. In the contemporary age, the Muslim Ummah is facing a lot of internal and external challenges and issues. The solution to these issues have been analyzed in the perspective of Seerat-e-Tayyibah (Biography of the Holy Prophet(SAAS)) with the focus on the responsibilities of our rulers, so we can relieve Muslim Ummah from all these problems and help them stand in the front line once again.